Speaking up to prevent harm: A systematic review of the safety voice literature. (August 2019) - Noort, Mark C.; Reader, Tom W.; Gillespie, Alex
Highlights: Safety voice is the act of speaking up about safety to prevent physical harm. Conceptually related to employee voice, safety voice has unique scope due to its emphasis on harm. It is ecological: predictors, pragmatics and outcomes are found across levels of analysis. Important challenges for safety voice remain in developing methodologies and interventions. Abstract: Safety voice is the act of speaking up about safety in order to prevent accidents and physical harm. It occurs across contexts (e.g., healthcare, aviation, construction, mountaineering, high-risk sports) and understanding the phenomenon enables interventions. Despite recent interest, however, it remains unclear how safety voice (i) differs conceptually from employee voice, (ii) is delineated across levels of analysis, and (iii) could be optimally investigated. Addressing this, we identified 48 articles, and integrated 256 safety voice antecedents, 7 pragmatics and 23 outcomes into an ecological framework. Overlap was found with employee voice concepts and methodologies, especially for the behavioural nature of speaking-up. Nonetheless, safety voice appeared unique in terms of the content of the raised message (e.g., limited to safety), the context and person speaking-up, identified antecedents (e.g., hazard-specific antecedents), and methodological challenges (e.g., operationalisation of victimhood). Our proposed safety voice framework provides a novel approach to safety voice that is ecological and indicates interventions for mitigating physical harm.